Optimalisasi pelaksanaan dokumentasi asuhan keperawatan di ruang rawat inap rumah sakit X Bandar Lampung - Ibrahim, Idris; Triyoso, Triyoso; Zainaro, Muhammad Arifki (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2023)
Background: Nursing care documentation is a record of the client's responses to nursing implementation activities in a comprehensive, systematic and structured manner as accountability for the actions taken by the nurse towards the client in carrying out nursing care using the nursing process approach. If documentation is not carried out completely, it will reduce the quality of nursing services because it will not be possible to identify the extent of the success of the nursing care that has been provided. In the legal aspect, nurses do not have written evidence if one day the client demands dissatisfaction with nursing services. Written proof of services provided to patients by nursing staff aims to avoid errors, overlaps and incomplete information. Purpose: To analyze and evaluate the optimization of the implementation of nursing care documentation in the Internal Medicine Inpatient Room at Hospital X in Bandar Lampung Method: This type of research uses a descriptive research design to investigate circumstances, conditions or other things that have been mentioned. The results are presented in the form of a research report. In descriptive research, phenomena include forms, activities, characteristics, changes, relationships, similarities and differences between one phenomenon and another. Research is carried out to determine the value of independent variables, either one or more variables (independent) without making comparisons, or connecting them with other variables. Meanwhile, the main aim of descriptive research is to systematically describe the facts and characteristics of the object or subject being studied accurately. The research was carried out in the Internal Medicine Inpatient Room at X Hospital Bandar Lampung in April 2023. Data was collected in various settings, sources and methods. Results: Most cases had complete medical record documentation of nursing care. A total of 45 (86.5%) of the nursing assessment documentation was complete. All nursing diagnosis documentation is complete. Data on planning documentation shows that almost all of them, 48 (92.3%) are also complete. Nearly 40 (76.9%) of the medical record status in nursing implementation documentation was complete. Finally, almost all 50 (96.2%) of the medical record status in the nursing evaluation documentation were also complete. Conclusion: The description of the documentation of care, assessment, diagnosis, planning, implementation and evaluation of nursing in the Internal Medicine Inpatient Room at Hospital X in Bandar Lampung shows that most of it is completely filled. Suggestion: It is hoped that the results of this research will be able to optimize the implementation of nursing care documentation in a systematic, comprehensive and complete manner for health services. Keywords: Documentation; Nursing Care; Patient Satisfaction. Pendahuluan: Dokumentasi asuhan keperawatan merupakan catatan tentang tanggapan/respon klien terhadap kegiatan-kegiatan pelaksanaan keperawatan secara menyeluruh, sistematis dan terstruktur sebagai pertanggunggugatan terhadap tindakan yang dilakukan perawat terhadap klien dalam melaksanakan asuhan keperawatan dengan menggunakan pendekatan proses keperawatan. Apabila pendokumentasian tidak dilakukan dengan lengkap akan dapat menurunkan mutu pelayanan keperawatan karena tidak akan dapat mengidentifikasi sejauh mana tingkat keberhasilan asuhan keperawatan yang telah diberikan. dalam aspek legal perawat tidak mempunyai bukti tertulis jika suatu hari nanti klien menuntut ketidakpuasan akan pelayanan keperawatan. Bukti tertulis pelayanan yang diberikan kepada pasien oleh tenaga keperawatan bertujuan untuk menghindari kesalahan, tumpang tindih dan ketidak lengkapan informasi. Tujuan: Untuk menganalisis dan mengevaluasi optimalisasi pelaksanaan dokumentasi asuhan keperawatan di Ruang Rawat Inap Penyakit Dalam Rumah Sakit X di Bandar Lampung Metode: Jenis penelitian ini menggunakan desain penelitian deskriptif untuk menyelidiki keadaan, kondisi atau hal lain-lain yang sudah disebutkan hasilnya dipaparkan dalam bentuk laporan penelitian. Dalam penelitian deskriptif fenomena ada yang berupa bentuk, aktivitas, karakteristik, perubahan, hubungan, kesamaan dan perbedaan antara fenomena yang satu dengan yang lainnya. Penelitian dilakukan untuk mengetahui nilai variabel mandiri, baik satu variabel atau lebih (independen) tanpa membuat perbandingan, atau menghubungkan dengan variabel yang lain. Sedangkan tujuan utama penelitian deskriptif menggambarkan secara sistematis fakta dan karakteristik objek atau subjek yang diteliti secara tepat. Penelitian dilaksanakan di Ruang Rawat Inap Penyakit Dalam Rumah Sakit X Bandar Lampung pada bulan April 2023. Pengumpulan data didapatkan dalam berbagai setting, sumber dan cara. Hasil: Sebagian besar kasus memiliki status rekam medis dokumentasi asuhan keperawatan yang lengkap. Sebanyak 45 (86.5%) pada dokumentasi pengkajian keperawatan adalah lengkap. Pada dokumentasi diagnosa keperawatan seluruhnya lengkap. Data pada dokumentasi perencanaan menunjukan hampir seluruhnya sebanyak 48 (92.3%) juga lengkap. Hampir seluruhnya sebanyak 40 (76.9%)  status rekam medis pada dokumentasi implementasi keperawatan adalah lengkap. Terakhir hampir seluruhnya sebanyak 50 (96.2%) status rekam medis pada dokumentasi evaluasi keperawatan juga lengkap. Simpulan: Gambaran dokumentasi asuhan, pengkajian, diagnosa, perencanaan, implementasi, dan evaluasi keperawatan di Ruang Rawat Inap Penyakit Dalam Rumah Sakit X di Bandar Lampung menunjukan sebagian besar terisi lengkap.   Saran: Hasil penelitian ini diharapkan mampu mengoptimalkan pelaksanaan dokumentasi asuhan keperawatan secara sistematis, komprehensif dan lengkap bagi pelayanan kesehatan.